2004
DOI: 10.1124/mol.65.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Site withinN-Methyl-d-aspartate Receptor Pore Modulates Channel Gating

Abstract: N-methyl-D-aspartate-type glutamate receptors (NMDARs) are ligand-gated ion channels activated by coagonists glutamate and glycine. NMDARs play a critical role in synaptic plasticity and excitotoxicity, largely because of their high calcium permeability and slow deactivation and desensitization kinetics. NR1 is an obligate subunit in all NMDAR complexes, where it combines with NR2A, 2B, 2C, and/or 2D. NR1 binds glycine, and residue Asn598 in the re-entrant membrane loop M2 largely determines NMDAR calcium perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…As shown in Fig. 5, A and B, we found, somewhat unexpectedly but similar to previously reported results (24), that the mutations, especially N616Q, made the resulting receptors more sensitive to agonists. The mean EC 50 values for glutamate and glycine were 0.19 and 0.33 µM (N616Q) and 1.1 and 0.73 µM (N616R), respectively.…”
Section: +supporting
confidence: 91%
“…As shown in Fig. 5, A and B, we found, somewhat unexpectedly but similar to previously reported results (24), that the mutations, especially N616Q, made the resulting receptors more sensitive to agonists. The mean EC 50 values for glutamate and glycine were 0.19 and 0.33 µM (N616Q) and 1.1 and 0.73 µM (N616R), respectively.…”
Section: +supporting
confidence: 91%
“…These regions include the LIVBP-like domain, the pre-M1 region, the lurcher site in the third transmembrane domain, and a methionine (Met823) in the fourth transmembrane domain (Krupp et al, 1998;Villarroel et al, 1998;Kohda et al, 2000;Zheng et al, 2001;Ren et al, 2003). Similar results have been obtained by introducing mutations in the P-loop (Asn598) or the lurcher site of NR1 (Kohda et al, 2000;Chen et al, 2004). The pre-M1 region of NR2A is a particularly attractive candidate for coupling ligand binding to channel gating because it links the glutamate-binding S1 domain to the channel.…”
supporting
confidence: 61%
“…In spite of the minor increase in glutamate potency, the rise time of glutamate-activated currents was slower in the presence of NR1(R), indicating that NR1(R) probably did not increase the glutamate binding rate. A concurrently performed study on recombinant NR1(R)/NR2A receptors observed very similar changes on kinetics and glutamate potency (Chen et al 2004). In this study, a kinetic model explained the leftward shift in the glutamate dose-response curve by a about 10-fold reduction in the channel closing rate, even without any modification in ligand binding and unbinding rates.…”
Section: Figure 1 I-v Relationships Of Nmda Currents Under Physiologsupporting
confidence: 50%